A Case Study of New Trends in Housekeeping Department of Hotel Radisson Blu, Kaushambi post COVID-19 Situation for Better Guest Service Experience (Global Journal of Management and Business Research, 2022)
This examination has been completed in the approach of continuous patterns in the hospitality industry in the face of COVID-19 situations. Hotel is the Housekeeping Department wills I became the front line of the new general hotel experience after the post COVID-19situations. Guests will seek out hotels that prioritise their health and safety by implementing reasonable and systematic cleaning and sanitation procedures. Keeping in mind the brain and hygiene protocol, there will be strict rules on the part of the hotel to maintain all standard operating processes. As a result, governments and businesses took harsh measures to mitigate the virus's impact and the resulting business loss. Hotel Housekeeping needs to meet major challenges, new trends and echo-friendly practice, housekeeping, training, employee's performance need to meet best practices. The first thing that guests come to our mind when we talk about the termicous housekeeping then it is clean. This department is behind the house. Every times we entering a five-star hotel, there are a few reasons why its still looks new and for the housekeeping department every time.
Keywords: new trends in housekeeping; COVID-19 pandemic; hospitality industry; impact; tourism